Pengembangan Urban Farming Kampung Sayur Berdasarkan Preferensi Masyarakat Kecamatan Gubeng Kota Surabaya - Rohadatul Aisy; Teguh Soedarto; Risqi Firdaus Setiawan (JURNAL RISET INDRAGIRI, 2023)
Indonesia is an agricultural country with fertile soil and rich natural resources, especially in theagricultural sector. One of the efforts made is to hold an urban farming program (urban farming).Carrying out urban battles is motivated by the problem of poverty in urban areas. The community'spreference for carrying out the urban farming program that is needed is very important, this isintended so that the community is willing and plays an active role in its implementation. The methodused in this study is descriptive qualitative analysis and Confirmatory Factor Analysis (CFA). Basedon the results of the Confirmatory Factor Analysis (CFA) analysis, there are several reducedvariables. This means that these variables are not in accordance with the preferences of the people ofGubeng District. Variables that are not suitable or have no effect according to the preferences of thepeople of Gubeng District are urban farming locations on government land and conventionaltechniques in urban farming.